Positional Therapy in Obstructive Sleep Apnea - de Vries, Nico; Ravesloot, Madeline; van Maanen, J. Peter (Springer International Publishing : Imprint: Springer, 2015)
Obstructive Sleep Apnea (OSA) is the most prevalent sleep disordered breathing disorder. It has become apparent that in more than half the patients with OSA, the frequency and duration of apneas are influenced by body position.  To treat patients with Position Dependent OSA (POSA), positional therapy can be considered for preventing patients from sleeping in the worst sleeping position. Recently, treatment of POSA has advanced dramatically with the introduction of a new generation of positional therapy.   Positional Therapy in Obstructive Sleep Apnea presents improved OSA diagnostic methods and the tools needed to implement positional therapy in clinical practice.  This includes patient work-up, positional therapy with or without other treatments, consequences of guidelines, and future developments.  Clinicians, students and researchers will find this comprehensive guide to be an invaluable resource for evaluating and treating sleep breathing disorders.